Applying The Constructivist Activities on Teaching English Literature A Study is Conducted in Literature Class of English Education Department of Universitas Negeri Manado - Delli Sabudu (English Education Postgraduate Program, Universitas Negeri Manado, 2024)
The aim of this research is to find out whether the constructivist theory is effective to enrich students mastery of literary work or not This research is classified as quantitative research which is true experimental design the data collected in the form of numbers and the data statistically analyzed In this research the writer used a sample of students in the parallel class of English Education students in the 3th semester who had learned the subject of Introduction to Literature One class randomly chosen from 4 clasess as the experimental class and control class and the t test observe used in analyzing the data < em>The research finding shows that students were given a pre test to what extent they understood about English Literature from the results obtained it was known that there were differences in mastery of the field of literature in each individual Then the students are given treatment using the constructivist theory referring to the students learning experiences about the work of English Literature given exposure and then post test results which can show the experimental group gets the majority of scores higher than the control group This means that there are significant differences between students interest in learning about English Literature has increased in mastery of the topic and the overall phenomena that accompany it In other words students who are taught using Constructivist theory master the topic or material better even they can enjoy the learning process more than Students who are not taught using Constructivist theory< em>< p>